The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00520-016-3487-5
|View full text |Cite
|
Sign up to set email alerts
|

Participation in treatment decision-making among Chinese-Australian women with breast cancer

Abstract: Intervention to improve doctors' cultural sensitivities in order to help them assess women's role preferences in TDM and the ability of doctors to communicate in a culturally appropriate manner, may improve the process of breast cancer TDM among women from Chinese background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 25 publications
2
38
0
1
Order By: Relevance
“…In Confucian morality systems, people tend to be reluctant to make medical decisions and instead leave them to clinicians. 28 This attitude has been conceptualized in recent studies as relational autonomy. 29 This perspective recognizes that self-determination is defined in a social context (ie, ethnicity, familial positioning, etc) and that this context influences the expressions or development of autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…In Confucian morality systems, people tend to be reluctant to make medical decisions and instead leave them to clinicians. 28 This attitude has been conceptualized in recent studies as relational autonomy. 29 This perspective recognizes that self-determination is defined in a social context (ie, ethnicity, familial positioning, etc) and that this context influences the expressions or development of autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to understand the specific cultural and language drivers that influence treatment shared decision-making among Asian American men with prostate cancer. For example, in some Asian cultures, the role of the family is a key determinant to the decision-making process [42,43]; and patients’ expectations of their provider’s roles can significantly influence the decision-making process, as some Asian patients may perceive offers of different treatment options as doctors’ incompetence [44]. …”
Section: Discussionmentioning
confidence: 99%
“… 15 17 Some of the barriers include language difficulties, health literacy, complexity of health care systems, and degree of acculturation. 18 A study by Claramita et al among patients and physicians in Indonesia, a neighboring country of Malaysia, reported that doctor–patient communication was affected by the cultural characteristics of the patients. 19 Therefore, this study investigated the perceived and preferred involvement level of breast cancer patients in the treatment decision-making process, sociodemographic factors that influence treatment decision-making, and the concordance between patients’ and physicians’ perspectives in decision-making.…”
Section: Introductionmentioning
confidence: 99%